Heuristic Approach to Comparing the Environmental Impacts of Carbon Nanotube Production Methods - Fikri, Ahmad Atif; Fadlika, Irham; Saeful, Albarrobi Nabila; Muhdi, Krisna Dwipa; Pratama, Daniel Febrian; Bello, Nasir Garba (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Carbon Nanotubes (CNTs) production so far has its own advantages and disadvantages. Some methods that can be used in producing CNTs are chemical vapor deposition (CVD), laser ablation, and arc discharge. The three methods have their own requirements, this causes different environmental impacts on each method. Studies into the environmental impact of the CNTs production process found that during thermal pretreatment of the reactant gas, more than 45 by-products were formed, including methane, volatile organic compounds, and polycyclic aromatic hydrocarbons. Calculating the environmental impact of CNTs production method often has challenges in implementation, because each production process has different systems and needs. One way to overcome this problem is by using the heuristic method for forecasting environmental impact, which can be done with the Multi-Criteria Decision Analysis algorithm. The method can calculate uncertainty in each scenario, by normalizing the given load value. In this study, the CVD method has the best solution and objective value results compared to laser ablation and arc discharge. The best solution and objective values that show the value of scenario quality and environmental impact in each method, in CVD the solution obtained in the 34th generation has an epsilon value of 0.00251. The generation shows the performance of the scenario, while the epsilon value shows the value of the environmental impact, the smaller the generation, the better the scenario, while the smaller the epsilon value, the smaller the environmental impact.